"Il segno di Menelik": Enrico Corradini, the Protocolos, and the Re-Staging of Adwa in São Paulo. (2nd January 2023) - Riccò, Giulia
Abstract : This essay brings to light how the Italian loss at Adwa of 1896 inspires Enrico Corradini to reimagine the dream of an imperial Italy in his novel La patria lontana (1910). By turning to a little-known episode in the history of Italo-Brazilian relations that forms part of the backdrop for La patria lontana, this essay reveals that Brazil functions as a stand-in for Ethiopia in Corradini's imaginary. In this highly Africanized, tropical, South American country, where large numbers of Italians had confronted hostile and resistant natives at the turn of the twentieth century, Corradini discovered a space that offered an opportunity to restage the First Italo-Ethiopian War as one in which Italians emerge victorious.